Desenvolvimento de métodos analíticos verdes empregando imagens digitais no infravermelho e visível para o controle de qualidade de alimentos e produtos farmacêuticos - Oliveira, Alessandra Stangherlin (2023)
The development of portable and easy-to-use devices is an important topic in the field of chemical analysis, given the possibility of carrying out field evaluations. This work describes the development of new portable devices using infrared and visible digital images. Thermal infrared enthalpimetry was carried out in pipette tips (In-tip TIE, In-tip thermal infrared enthalpimetry) for the determination of acetic acid in different types of vinegar, ascorbic acid in effervescent tablets of vitamin C, chlorides in nasal solutions and soy sauces, as well for the determination of alcohol content in distilled and fermented beverages. For this purpose, the pipette tips were filled internally with a piece of filter paper to retain a solution with a stoichiometric excess of reagent in two modes (with the paper wetted or dried with the reagent). Subsequently, the sample was aspirated into the tip. The reaction occurred during the mixing of the sample with the reagent inside the tip, and the temperature generated was monitored with a thermographic camera. The results obtained with in-tip TIE showed an agreement of 98 to 107% with the official methods. In this way, a new TIE platform could be developed that does not require the use of magnetic bars and stirrers for sample homogenization. In addition, other methods using colorimetry (DIC, digital image colorimetry) and infrared images (TIE in microplates) were proposed to determine dipyrone in oral pharmaceutical solutions. A system containing an LED lamp inside a white box, and a smartphone for capturing images was used. Optimization parameters (RGB channel selection and aspect ratio) were employed in order to guarantee reproducible results. The images were converted into red, green, and blue (RGB) histograms, constructed using the free PhotoMetrix® application. The results obtained were compared with the reference method, showing satisfactory results for the determination of dipyrone in pharmaceutical products, with agreements of 95 to 105% when compared to the conventional method. Through DIC and TIE it was possible to obtain analytical data from the same reaction quickly. Moreover, it was possible to perform the analyses with a significant reduction in the consumption of samples, reagents, and energy expenditure, in addition to allowing to carry out of analyses in the field due to potential portability.